Seventies Rule for the Establishment of Non-Native Marine Species - Stan Coppis; Arjan Gittenberger (Diversity)
Invasive non-native marine species have significant and far-reaching impacts on ecosystems, recreation, human health, and various industries worldwide. To mitigate this, it is crucial to be able to predict the likelihood of the establishment of non-native species. To that end, we reviewed twenty-two published lists of non-native species from the NE Atlantic and Mediterranean, plus five from other seas and oceans. From 1991 to 2020, 76% of the newly detected species in the NE Atlantic and Mediterranean, on average per region, became established. Similar rates were found for the Baltic Sea, New Zealand, South Africa, and Brazil, respectively: 77%, 73%, 73%, and 67%. A rate of 100% was reported for the Black Sea, however. While percentages fluctuate across regions, they do not significantly seem to differ over time within regions. Where available, using historical data is therefore recommended, taking into account regional circumstances. As a preliminary indicator, we propose the Seventies Rule for predicting the establishment success of newly detected species in the NE Atlantic and Mediterranean. With only five datasets from other areas in our studies, global applicability remains to be demonstrated. Policymakers, managers, and researchers can use our findings to predict establishment and decide on actions for invasive non-native marine species.